ANALISA HUKUM PELAKU TINDAK PIDANA PENGANIAYAAN KEPADA SESEORANG DITINJAU DARI PASAL 351 AYAT (1) KUHP (STUDI KASUS PUTUSAN NOMOR : 287/PID.B/2016/PN.JKT.SEL) - Martina Azizah; Sudarto (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
This study aims to find out and understand and examine the legal regulation of the Crime of Persecution in the Criminal Code, analyze the suitability of the application of the Law in Decision Number: 287/Pid.B/2016/PN.JKT.Sel with Legal Provisions. The background further analyzes the conformity of the Law of Perpetrators of Crimes of Persecution with legal provisions, reviewed from Article 351 paragraph (1) on the defendant Rizal Irfan Shahab Bin Muhammad who beat the victims Yani Mulyani Als Vanesa, and Vindi Namirah Isman. In this case, the defendant persecuted Vindi Namirah Isman in the form of a hairpin and beating on the temples of the eyes and ears, and Yani Mulyani Als Vanesa in the form of beating on the forearm, left and right, left and right hand, and fingers of the right hand, right and left lower limbs, and left knee, pain in the tailbone, resulting in Yani Mulyani Als Vanesa's death unconscious. based on Visum Et Repertum from dr. Binsar, a doctor at Jakarta Hospital Therefore, the defendant was then sentenced to 2 (two) months in prison. This research is a normative juridical legal research, or conducted by researching secondary data sources, consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection techniques used are document studies and literature studies, the instrument of this research is the decision Number: 287/Pid.B/2016/PN JKT.Sel The results of this study show, first, the provisions of the criminal law against the crime of persecution that have been regulated in article 351 paragraph (1) of the Criminal Code with the result of not causing serious injury and not dying to a person can be punished with a maximum prison sentence of 2 years and 8 months or a maximum fine of four thousand five hundred rupiah, the penalty can be increased If the act results in serious injuries, then the guilty person is threatened with imprisonment for a maximum of 5 years and if the act results in death for a maximum of 9 years. Second, the sentencing by the Judge in Decision Number: 287/Pid.B/2016/PN JKT.Sel are not in accordance with the provisions of the law and do not fulfill the sense of justice based on the theory of retributive justice.